Exploring Children’s Sense of Place With Qualitative Spatial Methods - Schicketanz, Juliane; Kabisch, Sigrun; Lakes, Tobia (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
Children sense their environment differently than adults. Despite a growing number of studies on children’s environmental perception, there is limited research on characterizing and methodologically addressing their perception and sense of place. The aim of this study is to characterize children’s sense of place and identify key benefits and challenges of qualitative spatial methods for assessing children’s sense of place. We explore children’s sense of place in the context of active mobility based on a literature review and the authors’ experiences of empirical case studies. Our findings highlight the influence of children’s cognitive development on their spatial knowledge, often oriented on landmarks. Children’s spatial stories are rooted in past experiences in space. Their perceptions originate from multisensory experiences. Children develop their own place meanings, partly independent of the intended purposes of those places. In addition, place attachment, shaped by memories and encounters, develops particularly through interaction with the environment independent of parents. This knowledge is important for geographical research, but also for urban planning, environmental education, and health promotion.